If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(17p + 15) + -16 = 6(14p + 7) Reorder the terms: 5(15 + 17p) + -16 = 6(14p + 7) (15 * 5 + 17p * 5) + -16 = 6(14p + 7) (75 + 85p) + -16 = 6(14p + 7) Reorder the terms: 75 + -16 + 85p = 6(14p + 7) Combine like terms: 75 + -16 = 59 59 + 85p = 6(14p + 7) Reorder the terms: 59 + 85p = 6(7 + 14p) 59 + 85p = (7 * 6 + 14p * 6) 59 + 85p = (42 + 84p) Solving 59 + 85p = 42 + 84p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-84p' to each side of the equation. 59 + 85p + -84p = 42 + 84p + -84p Combine like terms: 85p + -84p = 1p 59 + 1p = 42 + 84p + -84p Combine like terms: 84p + -84p = 0 59 + 1p = 42 + 0 59 + 1p = 42 Add '-59' to each side of the equation. 59 + -59 + 1p = 42 + -59 Combine like terms: 59 + -59 = 0 0 + 1p = 42 + -59 1p = 42 + -59 Combine like terms: 42 + -59 = -17 1p = -17 Divide each side by '1'. p = -17 Simplifying p = -17
| 2x+3y+12+3x+6y-7= | | -6(10h-20)=-18h-6 | | 8+3=y | | -5(-19j+11)+20j=4(14j+1) | | 17-(6x+6)=16 | | 9m+10=62 | | 9y+5(-y+16)=-4y | | .75x+1.5= | | 3/7x21.21 | | 3(-11u-5)+14u=-20u | | -12-4x=-41x+576 | | (3n+9)(2n+4)=84 | | 6(-5k-18)-18=9-17k+2k | | 48a^2x-20ax-12x=0 | | 10-7(-4t-15)=-15+18t | | -23+5x=62 | | 7(-4q+12)-14q=6(-8q+19) | | -14.6s-13.46=-12.7s+16.94 | | -10.4b=7.74-9.5b | | -2.7m-6.9m+19.73=-2.4m+16.13 | | 396=9x+27 | | m^2-11m-26=0 | | 11.04+7.5d=6.7d | | 2.2z+15.54=0.8z-11.9 | | 12x+3y-9x-7y= | | -2x=25/42 | | 9c=8c-11 | | 6x+4y-9x-4y= | | 8+2n=-14+9n-20 | | 10+8r=r-18 | | 7t+5g-2g-5t= | | 16p+12q+p-7q-5p= |